Finite Element Method Based Slope Stability Analysis of Crack Soil: Tana Toraja – Enrekang Road KM 240+400 - Oktavian Dwi Saputro; Mohamad Khoiri; Dwa Desa Warnana (Potensi: Jurnal Sipil Politeknik, 2026)
Indonesia is a region with mountainous topography and high rainfall, a condition that naturally increase vulnerability to landslides. However, conventional slope stability assessments often produce inaccurate safety predictions because they tend to ignore the existence of macro structures such as cracked soil. This study investigates the landslide trigger mechanism on Tana Toraja – Enrekang road at STA 240+400 using finite element modeling via Plaxis 2D. The mechanical behavior of intact slope scenarios is compared against slopes with varying crack depths to evaluate worst-case stability boundaries. Numerical results demonstrate that even under fully saturated intact soil conditions, the slope remains stable with a Safety Factor (SF) of 1.181. Conversely, critical conditions leading to collapse (SF = 0.998) are reached when 9-meter deep cracks are fully infiltrated by rainwater. The analysis indicates that this instability is strongly driven by a critical combination of soil cohesion loss and hydrostatic water pressure acting as an active driving force within the cracks. These findings demonstrate the cracked soil mechanism is a determining factor for landslides at this site, highlighting the necessity of integrating crack depth thresholds into early warning and surface mitigation strategies